Chirurgie Duanova retrakcního syndromu I: Srovnání jednostranné retropozice a resekce s oboustrannou retropozici mediálních prímých svalů - Vodicková, K; Autrata, R; Rehůrek, J (Ceska a slovenska oftalmologie, 2008)
The purpose of this comparative study was to evaluate a long-term efficacy of lateral rectus muscle resection in the affected eye of patients with Duane retraction syndrome (DRS) with esotropia and limited abduction and to compare it with bilateral medial rectus recessions. We reviewed and compared the data of the group A with 23 patients who underwent a recession-resection procedure and the group B with 26 patients in whom we performed medial rectus recessions. In each group, we evaluated pre- and postoperatively the ocular alignment, head position, ocular ductions, severity of retraction, and binocular visual field. Statistical analysis of the data was performed. Postoperatively, both groups had similar mean esotropia and mean face turns. However, the mean limitation of abduction in the affected eye was greater in the group B, mean adduction was also significantly worse in the group B. Globe retraction improved in all subjects of the group B, but worsened in 6 patients of the group A. Seventeen of 23 patients with Duane retraction syndrome, selected on the basis of esotropia, limited abduction, and mild retraction, benefited from a recession-resection procedure in the affected eye. The ability of abduction achieved higher level than in the group B after bilateral medial rectus recessions. We assume that unilateral recession-resection procedure should be performed in patients with mild retraction of the globe and good preoperative adduction.
Keywords: dítě; předškolní dítě; Child; Oculomotor Muscles; lidé; okulomotorické svaly; Adolescent; Humans; Duane Retraction Syndrome; Child, Preschool; Duaneův retrakční syndrom; mladiství